2023
DOI: 10.1002/admi.202202399
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Based Synthesis of Freestanding Graphene from a Natural Resource for Sensing Application

Abstract: The bottomup approach, that is, modified Hummers' method, is a well-established chemical synthesis technique to synthesize graphene. However, this technique, not only utilizes strong acids and oxidants [4,5] but also entails numerous steps of synthesis such as dilution, mixing, oxidation, reduction, washing, centrifuging, and intense stirring. [6] On the other hand, some of the bottom-up methods, in particular, chemical vapor deposition (CVD) and plasma-enhanced chemical vapor deposition (PE-CVD) are expensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Doping of carbon materials with nitrogen (NÀ ) may have more than one precursor or require several steps to synthesize, which are very costly. Recently, Jacob et al demonstrated the Single-step and single-precursor synthesis of N-doped graphene oxide (N-GO) by aniline as the source of carbon and nitrogen at ambient conditions [32]. Herein, we synthesized nitrogen-containing carbon nanolayers modified graphdiyne nanostructure as new co-reactant for development of ECL platform.…”
mentioning
confidence: 99%
“…Doping of carbon materials with nitrogen (NÀ ) may have more than one precursor or require several steps to synthesize, which are very costly. Recently, Jacob et al demonstrated the Single-step and single-precursor synthesis of N-doped graphene oxide (N-GO) by aniline as the source of carbon and nitrogen at ambient conditions [32]. Herein, we synthesized nitrogen-containing carbon nanolayers modified graphdiyne nanostructure as new co-reactant for development of ECL platform.…”
mentioning
confidence: 99%